Effectiveness of deep cryogenic treatment on carbide precipitation - Patricia Jovičević-Klug; Matic Jovičević-Klug; Bojan Podgornik (Journal of Materials Research and Technology, 2020)
The study discusses the effectiveness of deep cryogenic treatment (DCT) on selected steels and its effectiveness on carbide precipitation. The investigation of DCT influence on the precipitation of different carbide types in three selected high-speed steels (M2, M3:2 and M35) has been carried out by a combination of x-ray diffraction (XRD), scanning electron microscopy (SEM), fractography, energy-dispersive X-ray spectroscopy (EBSD) and transmission electron microscopy (TEM). Three different steels with different chemical composition were selected in order to observe and correlate DCT induced carbide precipitation phenomena with varying concentration of alloying elements (Co, Cr, Mo, V and W). The study discloses the DCT effect on carbide distribution, morphology, size, and the mechanism of their formation. Using thermodynamic modeling the precipitation and origin of specific carbides is discussed and confirmed. This research proves that DCT has an impact on precipitation of carbides by increasing their volumetric fraction (overall up to 23%, up to 140% for M23C6), density (up to 30% for MC and M6C carbides), reducing their mean size and inducing a more homogeneous distribution of them. Low-cobalt-bearing steels exposed to DCT display an increased volume fraction of M23C6 carbides that presumably originate from the precipitation of additional embryos formed during DCT. However, selected steel with high Co content showed no significant changes in the volumetric fraction of carbides after DCT. The impact of preexisting M2C carbides and their decomposition on the final carbide formation is also discussed.